Contextual factors influencing the success of global product development. (2018) - Sbernini, Federico; Granini, Nicola; Herbert-Hansen, Zaza Nadja Lee; Khalid, Waqas
The purpose of this paper is to identify the contextual factors that determine the success of global product development (GPD) process. By adopting an exploratory inductive research, founded on core literature in the area and using empirical data from four companies in different industries, the paper contributes to GPD theory by examining the factors that drive different GPD configurations, extends GPD success factors in a global context, and proposes a novel framework useful for practitioners in the process of planning for global activities. The shift towards a global GPD strategy results in a series of interrelated changes which are strictly connected with the company's source of competitive advantage, their globalisation drivers, the globalisation practices adopted which create a global network, and the series of organisational capabilities needed to support the globalisation and the externalisation of knowledge sources.